2017
DOI: 10.1111/psyp.12906
|View full text |Cite
|
Sign up to set email alerts
|

Theta‐ and delta‐band EEG network dynamics during a novelty oddball task

Abstract: While the P3 component during target detection and novelty processing has been widely studied, less is known about its underlying network dynamics. A recent cognitive model suggests that frontal-parietal and frontal-temporal interregional connectivity are related to attention/action selection and target-related memory updating during the P3, respectively, but empirical work testing this model is lacking. Other work suggests the importance of theta- and delta-band connectivity between the medial frontal cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 83 publications
8
50
1
Order By: Relevance
“…These results are consistent with predictions from the parieto-frontal integration theory of intelligence (P-FIT; , which proposes that effective interactions between frontal and parietal brain regions underlie individual differences in intelligence. Because synchronized theta activity has been associated with the coupling of frontoparietal and frontotemporal functional networks (Güntekin & Başar, 2010;Harper et al, 2017), our results are consistent with neuroimaging studies that found associations between the connectivity of frontoparietal cognitive control networks and intelligence (Cole et al, 2012;Hilger et al, 2017b;Pineda-Pardo et al, 2016;Wendelken et al, 2017) and support the notion that efficient information transmission between these networks contributes to greater intelligence.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are consistent with predictions from the parieto-frontal integration theory of intelligence (P-FIT; , which proposes that effective interactions between frontal and parietal brain regions underlie individual differences in intelligence. Because synchronized theta activity has been associated with the coupling of frontoparietal and frontotemporal functional networks (Güntekin & Başar, 2010;Harper et al, 2017), our results are consistent with neuroimaging studies that found associations between the connectivity of frontoparietal cognitive control networks and intelligence (Cole et al, 2012;Hilger et al, 2017b;Pineda-Pardo et al, 2016;Wendelken et al, 2017) and support the notion that efficient information transmission between these networks contributes to greater intelligence.…”
Section: Discussionsupporting
confidence: 90%
“…Phase-synchronized oscillatory activity is a prime candidate for the facilitation of interregional goal-directed information processing associated with cognitive control processes (Cole et al, 2012;Hilger et al, 2017b;Pineda-Pardo et al, 2016;Wendelken et al, 2017), because it coordinates interregional communication and information-transfer in specific time windows (Fries, 2005). In particular, synchronized oscillatory activity in the thetaband has been suggested to underlie the functional networks associated with the P3 (Harper, Malone, & Iacono, 2017), with the medial frontal cortex acting as a central hub for long-range information transmission (Cohen, 2011;Helfrich & Knight, 2016). The connectivity degree as a measure of relative functional connectivity reflects the extent to which an area acts as a global hub in information-processing, with greater connectivity degrees indicating greater centrality (greater "hubbiness") of a node in goal-directed information-processing.…”
Section: The Present Studymentioning
confidence: 99%
“…The role of theta bursts in cognitive control has been the target of extensive investigation over the last few years. Several articles have shown that theta bursts (typically lasting a few hundred milliseconds) are associated with conflict or with conditions requiring enhanced cognitive control (e.g., Harper, Malone, & Iacono, ; McDermott, Weisman, Proskovec, Heinrichs‐Graham, & Wilson, , Töllner et al, ). Although some authors (e.g., Töllner et al, ) have linked these increases in theta activity to conflict monitoring per se, others have linked the amplitude of this signal to task complexity (e.g., Cooper et al, —who also reported an increase in delta activity; Voytek et al, ), task switching (e.g., Cunillera et al, ), or in some cases to the anticipation of conflict (e.g, Chang, Ide, Li, Chen, & Li, ).…”
Section: Interactions Between Phasic Burst and Oscillatory Phenomenmentioning
confidence: 99%
“…Studies using intracranial EEG have shown that hippocampal theta power is increased during encoding of contextually unexpected information (Axmacher et al, 2010;Chen et al, 2013). Furthermore, contextually unexpected events elicit increases in scalp-recorded frontal theta power (e.g., Cavanagh et al, 2012;Walsh & Anderson, 2012;Cavanagh & Frank, 2014), and recent EEG studies have demonstrated increases in theta phase synchrony between frontal and temporal scalp sites during contextually unexpected stimuli (Lee et al, 2014;Harper et al, 2017). In light of this evidence, it is possible that theta oscillations facilitate communication between the prefrontal cortex and hippocampus during encoding of contextually unexpected events.…”
Section: Introductionmentioning
confidence: 99%